1985
DOI: 10.1093/ajcp/83.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Paget’s Cells: New Evidence Linking Mammary and Extramammary Paget Cells to a Common Cell Phenotype

Abstract: Three mouse monoclonal anti-human cytokeratin antibodies were made against human sole epidermis. One of these (KA4) was shown to react with a variety of human simple epithelium, including eccrine and apocrine sweat glands and the luminal cells of the breast ducts and lobules, but failed to decorate interfollicular stratified squamous epithelium. This antibody reacted by the immunoblot technic with cytokeratins of Mr values 54, 46, and 40 kdaltons. KA4 reacted strongly with clear cells found in 11% of breast ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 0 publications
1
25
1
1
Order By: Relevance
“…In brief, for the generation of anti-cytokeratin 6 (clone KA 12) antibodies, keratins were isolated from human foot sole epidermis using the salt extraction method described by Sun and Green (1978). Immunization and the production of monoclonal antibodies against cytokeratin 6a (clone KA12) were performed according to standard protocol (Nagle et al, 1985). For this study, we further used the following murine monoclonal antibodies: anti-cytokeratin 5 clone KA 2 (Fan et al, 1997); anti-human cytokeratin 19 conjugated to FITC (Abcam Ltd., Cambridge, UK).…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, for the generation of anti-cytokeratin 6 (clone KA 12) antibodies, keratins were isolated from human foot sole epidermis using the salt extraction method described by Sun and Green (1978). Immunization and the production of monoclonal antibodies against cytokeratin 6a (clone KA12) were performed according to standard protocol (Nagle et al, 1985). For this study, we further used the following murine monoclonal antibodies: anti-cytokeratin 5 clone KA 2 (Fan et al, 1997); anti-human cytokeratin 19 conjugated to FITC (Abcam Ltd., Cambridge, UK).…”
Section: Antibodiesmentioning
confidence: 99%
“…The rabbit antibodies specific for the α2 subchain of laminin 5 and the murine antibody against collagen VII (clone 9C3) were kindly provided by Dr. J. Jones (Northwestern University, Chicago, Il). The generation and purification of the rabbit polyclonal antibody 18 A, which reacts mainly with cytokeratin 5 and 14 but also with cytokeratins 8 and 18, was described by Nagle and coworkers (Nagle et al, 1985). The secondary antibodies we used for immunofluorescence microscopy were Alexa Fluor 568 goat anti-rabbit IgG, Alexa 488 and 350 goat anti-mouse IgG, and Alexa 488 anti-rat IgG (Molecular Probes, Eugene, OR).…”
Section: Antibodiesmentioning
confidence: 99%
“…However, in reports claiming K14 expression in matrix cells, an mAb (KA1) was used in the identification. This antibody seems to be of questionable specificity (see, for example, Nagle et al, 1984vs. Nagle et al, 1986.…”
Section: Absence Of Kl4 and 104 Mrna Expression In The Matrixmentioning
confidence: 99%
“…It is known, for example, that ORS cells express K5 and K14 (Moll et al, 1982b;Lynch et al, 1986;Stark et ai., 1987;Heid et al, 1988aHeid et al, , 1988bMoll et al, 1988;Kopan and Fuchs, 1989), and recently it was claimed that matrix cells also express K14 (Heid et al, 1988a(Heid et al, , 1988bMoll et al, 1988). However, it is not known whether the temporal and spatial expression of K5 and K14 in the ORS is similar to that of epidermis, and moreover, it is controversial whether matrix cells truly contain K14: the only antibody which has detected K14 in matrix is an mAb (KA1) whose antigenic specificity has not yet been fully analyzed (Nagle et al, 1984(Nagle et al, , 1986. That this antibody has not yet been well characterized becomes an especially important issue in light of findings by other researchers that (a) common antigenic epitopes exist between keratins and nonkeratin proteins in hair (Lynch et al, 1986) and (b) other K14-and K5-specific probes have not detected these or other keratins in matrix cells (Moll et al,, 1982b;Heid et al, 1986;Lynch et al, 1986;Kopan and Fuchs, 1989).…”
mentioning
confidence: 99%
“…Recently, it has been reported that Paget cells contain particular types of cytokeratins different from those of epidermis (16,17). Nagle et al (19) described that KA4 monoclonal keratin antibody (54, 46 and 40 kDa), reacted with Paget cells and suggested a common cellular phenotype. Kariniemi et al (10) stated that PKK1 and RGE53 monoclonal antibody to keratin reacted to Paget cells which suggesting mammary or sweat duct epithelium origin.…”
Section: Immunohistochemicalmentioning
confidence: 99%